P0107DIGITAL PATHOLOGY FOR THE ROUTINE DIAGNOSIS OF RENAL DISEASES: A STANDARD MODEL. (6th June 2020) - L'Imperio, Vincenzo; Ferrario, Franco; Nebuloni, Manuela; Pieruzzi, Federico; Sinico, Renato Alberto; Pagni, Fabio
Abstract: Background and Aims: Whole-slide imaging (WSI) and virtual microscopy are useful tools implemented in the routine pathology workflow in the last 10 years, allowing second-opinion on definitive or frozen-section diagnosis (telepathology) and demonstrating a substantial role in multidisciplinary (MDT) meetings and education (Griffin et al, Histopathology. 2017;70(1):134-145). The FDA approval of the clinical employment of this technology led to the progressive digitalization of routine pathological practice. In this setting, a recent work explored the usefulness of this technology applied to renal biopsies, stressing the possibility to create integrate networks to share cases for diagnostic and research purposes (Barisoni et al, Clin Kidney J. 2017;10(2):176–187). Here is discussed the 5-years experience of an Italian Renal Pathology service in which telepathology is a definitive standard of care. Method: Renal biopsies were collected in the Anatomic Pathology Department of San Gerardo Hospital, Monza, Italy from 14 different Italian Nephrology centers (9 from the North, 1 from the Center and 4 from the South of Italy) from January 2015 to December 2019. After the routing processing of the tissue, biopsies were scanned with Aperio CS2 device for light microscopy and Aperio ScanScope FL for immunofluorescence (Leica Biosystem, Illinois, USA, Figure 1A ). Digital slides were then imported in the Spectrum platform along with the final report and additional pictures (eg. electron micrographs and special stains) such as shown in Figure 1B . Results: In 5 years, 704 renal biopsies (interval 110-160) were scanned and analysed with a turnaround time of around 2-3 working days. The most frequent diagnosis was represented by MN (16%, 115 cases, interval 18-28) followed by IgA nephropathy (12%, 84 cases, interval 12-21), FSGS (9%, 66 cases, interval 8-18), MCD (8%, 54 cases, interval 7-13), paucimmune crescentic GN (7%, 48 cases, interval 6-13), diabetic nephropathy (6%, 45 cases, interval 6-12), lupus nephritis (5%, 37 cases, interval 5-11), arterionephrosclerosis (5%, 35 cases, interval 5-13), amyloidosis (5%, 32 cases, interval 3-7) and tubulointerstitial nephritis (4%, 28 cases, interval 4-6). Only 4% of cases (28, interval 4-10) were suboptimal for the diagnosis and the remaining 19% (132 cases, interval 20-36) were characterized by rarer diseases, as detailed in Figure 1C . Conclusion: In renal pathology the assessment of biopsies with different techniques (light and electron microscopy and immunofluorescence) is mandatory and can represent an obstacle in the routine employment of digital pathology. In the present experience we demonstrated the feasibility and sustainability of the digital switch in renal pathology routine, thanks to appropriate devices and platform. This led to store cases for teaching and MDT meetings, allowing to maintain the same short turnaround time for the diagnosis. Moreover, the employment of WSI technique can allow to couple the proteomic features of renal tissue with the classic morphological aspects of the diseased parenchyma (L'Imperio et al Proteomics Clin Appl. 2016 Apr;10(4):371-83). This approach, along with the possibility of a multicentric enrollment of patients, led to the publication of 6 scientific papers in highly impacted journals, further confirming the positive role of digital pathology in this field.